2011
DOI: 10.1007/s00221-011-2560-z
|View full text |Cite
|
Sign up to set email alerts
|

Is inefficient multisensory processing associated with falls in older people?

Abstract: Although falling is a significant problem for older persons, little is understood about its underlying causes. Spatial cognition and balance maintenance rely on the efficient integration of information across the main senses. We investigated general multisensory efficiency in older persons with a history of falls compared to age- and sensory acuity-matched controls and younger adults using a sound-induced flash illusion. Older fallers were as susceptible to the illusion as age-matched, non-fallers or younger a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
245
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(277 citation statements)
references
References 58 publications
28
245
4
Order By: Relevance
“…Moreover, given the known interactions between the main sensory systems and vestibular function (e.g. Lopez et al, 2012), as well as the efficiency by which sensory information is combined in the older brain (Diederich et al, 2008;Setti et al, 2011) these findings suggest the possibility that improving balance control in older adults may also affect multisensory function in general, possibly leading to a reduced risk of falling. The aim of the current study was to assess the impact of improved balance control, and therefore vestibular functioning, on the integration of information across two sensory systems which are important for spatial cognition, namely vision and audition, as measured by susceptibility to the SIFI.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, given the known interactions between the main sensory systems and vestibular function (e.g. Lopez et al, 2012), as well as the efficiency by which sensory information is combined in the older brain (Diederich et al, 2008;Setti et al, 2011) these findings suggest the possibility that improving balance control in older adults may also affect multisensory function in general, possibly leading to a reduced risk of falling. The aim of the current study was to assess the impact of improved balance control, and therefore vestibular functioning, on the integration of information across two sensory systems which are important for spatial cognition, namely vision and audition, as measured by susceptibility to the SIFI.…”
Section: Introductionmentioning
confidence: 98%
“…However, Poliakoff, Ashworth, Lowe, and Spence (2006) reported that when spatially incongruent inputs from different modalities are presented to older adults, then this can result in distractibility and inefficient processing of the target stimulus. More specifically, previous studies have reported that in comparison to healthy older adults, fall-prone older adults are less successful at integrating (Mahoney, Holtzer, & Verghese, 2014;Setti, Burke, Kenny, & Newell, 2011) or re-weighting (Jeka, Allison, & Kiemel, 2010) the relative reliability of information from visual, vestibular and proprioceptive inputs in response to changes in the environment. This inefficient re-weighting across sensory inputs may, in turn, affect postural stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been seen recently (Setti et al 2011) that audiovisual multisensory integration is less efficient in older subject who fall compared with older non-fallers. The perception of temporally distinct stimuli as concurrent was seen to happen for considerably longer temporal intervals, manifesting as the incorrect multisensory integration of stimuli separated by 270 ms. At this extended time scale, this could indicate a top-down problem in modulating the cognitive processing of sensory information, rather than a problem of sensory decline, and so the phenomenon may not be specific to audio-visual sensory modalities.…”
Section: Discussionmentioning
confidence: 99%